2009
DOI: 10.1002/pro.48
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidence suggests that antiactivator ExsD from Pseudomonas aeruginosa is a DNA binding protein

Abstract: The opportunistic pathogen P. aeruginosa utilizes a type III secretion system (T3SS) to support acute infections in predisposed individuals. In this bacterium, expression of all T3SS-related genes is dependent on the AraC-type transcriptional activator ExsA. Before host contact, the T3SS is inactive and ExsA is repressed by the antiactivator protein ExsD. The repression, thought to occur through direct interactions between the two proteins, is relieved upon opening of the type III secretion (T3S) channel when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 53 publications
(70 reference statements)
1
23
0
Order By: Relevance
“…With the use of a calibration curve obtained by analyzing a set of standard proteins, the retention time of the variant protein gave an apparent molecular mass of 42 kDa. Although this is somewhat larger than the actual 32‐kDa mass of an ExsD monomer, the discrepancy is readily explained by the distinctively nonglobular shape of the molecule . In contrast, wild‐type ExsD (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…With the use of a calibration curve obtained by analyzing a set of standard proteins, the retention time of the variant protein gave an apparent molecular mass of 42 kDa. Although this is somewhat larger than the actual 32‐kDa mass of an ExsD monomer, the discrepancy is readily explained by the distinctively nonglobular shape of the molecule . In contrast, wild‐type ExsD (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…A striking feature of ExsD is the apparent plasticity of its oligomeric state, depending on the interacting partner. ExsD forms a 2 : 2 complex with ExsC and a 1 : 1 complex with ExsA, whereas analytical ultracentrifugation studies and the ExsD crystal structure suggest that ExsD self‐associates to form a trimer in the absence of the other two proteins . Our recent work suggests that the ExsC–ExsD complex actually consists of two ExsD monomers bound to an obligate ExsC dimer, rather than a dimer of dimers .…”
Section: Resultsmentioning
confidence: 86%
“…The fact that ExsD is unable to bind ExsA unless both proteins are simultaneously expressed would suggest that de novo synthesis of ExsD is required for inhibition of T3SS gene expression. ExsD appears to have three fates when synthesized: ExsA binding, ExsC binding, or self-association into a trimer (1,37). One possibility to account for the data is that ExsD or ExsA preferentially binds to a folding intermediate of the cognate partner to form the 1:1 stoichiometric complex.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, the ExsD crystal structure revealed that the amino-terminus of ExsD has structural similarity to the DNA-binding domain of the KorB transcriptional repressor (Bernhards et al, 2009). The predicted DNA-binding interface, however, is buried within the trimeric structure suggesting that dissociation of the trimer might be required for ExsD to exhibit DNA-binding activity.…”
Section: Intrinsic Regulation Of T3ss Gene Expressionmentioning
confidence: 99%